Wpływ kryzysów globalnych na zmianę podejścia Unii Europejskiej do sytuacji kryzysowych. Aspekty prawne - Mik, Cezary (PRAWO i WIĘŹ, 2025)
The first quarter of the 21st century was a time of global crises that forced the EU to revise its previous individualist approach to crises. They not only caused a natural increase in the EU’s legislative and intervention activity in these circumstances but also contributed to conceptual and regulatory development both in relation to their different types and to the definition of a more horizontal, integrated approach. The Union’s contemporary approach encompasses the totality of possible crisis progression and recognizes the multisectoral impact of global crises and their interactions. Despite competence deficits, the EU has created its own crisis or emergency law. The paper analyzes the concept of crisis, its legal basis and the EU’s competence in relation to major global crises (financial, migration, pandemic, and climate crises resulting from armed conflicts). Changes in the Union’s approach to specific types of crises, the strengthening of crisis coordination mechanisms, and new acts based on the general concept of crisis (regardless of which crises are involved) and the belief in the need to protect certain values and interests of the Union (e.g., protection of the internal market, critical entities) are shown.